2007
DOI: 10.1080/14786410701189781
|View full text |Cite
|
Sign up to set email alerts
|

Callus ofSecurinega suffruticosa, a cell line accumulates dextro Securinega alkaloids

Abstract: Investigations on callus cultures of Securinega suffruticosa indicated that the cell line of S. suffruticosa callus was able to accumulate four known Securinega alkaloids with dextro rotation but not levo rotation as reported before: virosecurinine (1), viroallosecurinine (2), 14,15-dihydrovirosecurinine (3) and ent-phyllanthidine (4). Time course studies on the growth of callus cultures were carried out. The effects of different plant growth regulators, sucrose concentrations on callus growth and virosecurini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…In the present work, the combination of 0.5 mg l -1 IAA and 5.0 mg l -1 KIN provided the highest accumulation of S and AS among all PGR compositions tested. Positive effect on indolizidine alkaloid accumulation was also noted for NAA, confirming the results by Wysokińska (1979), Ide (1991) and Yuan et al (2007), as well as IPA whose influence on alkaloid metabolism has so far been scarcely investigated.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…In the present work, the combination of 0.5 mg l -1 IAA and 5.0 mg l -1 KIN provided the highest accumulation of S and AS among all PGR compositions tested. Positive effect on indolizidine alkaloid accumulation was also noted for NAA, confirming the results by Wysokińska (1979), Ide (1991) and Yuan et al (2007), as well as IPA whose influence on alkaloid metabolism has so far been scarcely investigated.…”
Section: Discussionsupporting
confidence: 70%
“…The influence of different combinations of the above PGRs on the growth and alkaloid content in S. suffruticosa callus was also investigated by other authors. Yuan et al (2007) found that at the constant KIN concentration, the increase in 2,4-D content resulted in slower growth rate and lower alkaloid concentration. In another study, Ide (1991) tested several compositions of 2,4-D and KIN, the best of which yielded 0.06 mg g -1 S (compared to 0.32 mg g -1 S in the present work).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations